Pengaruh Minat Baca terhadap Kemampuan Literasi Media Siswa SMK Swasta Sri Langkat Tanjung Pura - Siti Fauziah; Nursapia Harahap; Abdi Mubarak Syam (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The research was conducted at the Sri Langkat Tanjung Pura Private Vocational School. The purpose of this research is to determine the level of reading interest of students at Sri Langkat Tanjung Pura Private Vocational School, to determine the level of media literacy abilities of Sri Langkat Tanjung Pura Private Vocational School students, and to find out how much influence reading interest has on students' media literacy abilities at Sri Langkat Private Vocational School. Tanjung Pura. This research uses descriptive research methods with a quantitative approach. This quantitative approach emphasizes analysis in the form of numbers (numerical values) which are processed using statistical methods. In this case, researchers want to know how interest in reading influences students' media literacy skills at SMK S Sri Langkat Tanjung Pura. The results of this research show that interest in reading has gone well among students at the Sri Langkat Tanjung Pura Private Vocational School. This was shown in the presentation as many as 23.10% answered strongly agree, 74.01% answered agree, 02.78% answered disagree, while 00.11% answered strongly disagree. Because many students have the motivation to read, feel happy when reading reading sources, and are not forced to read. Media Literacy Skills have also gone well among Sri Langkat Tanjung Pura Private Vocational School students. This was shown in the presentation as many as 33.45% answered strongly agree, 65.48% answered agree, 01.07% answered disagree, while 00.00% answered strongly disagree. Because students already understand what kind of information they really need, students also know that information can only be obtained through any media such as books, the internet, newspapers, magazines or encyclopedias. And the influence of interest in reading on the media literacy abilities of Sri Langkat Tanjung Pura Private Vocational School students has a strong influence which can be seen from the influence test, t test results and the results of the coefficient of determination R2. The results of the t test of Reading Interest as an independent variable on Media Literacy Ability as a dependent variable show the results of the t count = 9.001 and t table = 1.987 (t count > t table) with a significance level of 0.000 < 0.05, so it can be concluded that Reading Interest has a strong influence on Literacy Ability Media or in other words H0 is rejected and Ha is accepted.